The Effect of Quadriceps Fatigue on Electromyographic Activity of Some Knee Joint Muscles during Stance Phase of Walking - Behrouz Hajilou; Mehrdad Anbarian; Hamed Esmaili; Sara Sadeghi (Sport Sciences and Health Research)
The aim of this study was to examine the effect of quadriceps fatigue on electromyographic parameters during stance phase of walking. For this purpose, 12 active men (age: 24.5±2.27 years, weight: 75.8±4.61 kg, height: 178.6 ± 6.46 cm) were selected. Leg extension machine was used to induce quadriceps fatigue with 50% of one – repetition maximum load. Surface electromyographic activity of rectus femoris, vastus medialis, vastus lateralis, biceps femoris, semitendinosus, medial gastrocnemius and tibialis anterior muscles were recorded during walking before and after fatigue protocol. Paired t test was used to analyze the data. The results showed a decrease in the activity of selected muscles after fatigue during stance phase of walking. It can be concluded that quadriceps fatigue was accompanied with lower activity of other muscles especially hamstring which can decrease knee joint stability during the stance phase of walking and consequently the probability of knee injury.